Abundant optical solitons to Biswas–Milovic model having parabolic law nonlinearity and spatio-temporal dispersion using improved modified extended tanh function scheme - Samir, Islam; Abdalla, Nesreen Sirelkhtam Elmki; Abd-Elmonem, Assmaa; Ahmed, Hamdy M. (Optik (Stuttgart), 2023)
The objective of this work is to examine the optical solitons of the Biswas–Milovic model, which has been the focus of many studies and continues to be important in this field of study of nonlinear optics. Besides the group velocity dispersion, spatio-temporal dispersion and parabolic law of nonlinearity effects are also added to this model. The improved modified extended tanh function scheme is applied to retrieve optical solitons and other exact wave solutions to the model. This method depends on the extended Riccati equation. So, various solutions can be extracted such as (bright, dark and singular) solitons, exponential, singular periodic, Weierstrass elliptic and rational type solutions. The graphical illustrations are depicted for some selected solutions to show the dynamics of the extracted solutions. The optical solitons produced in respect to this form have never been explored by the proposed technique before, and the results have never been published.